Evaluation of vibration on technological devices - Lukovics, Petr (Manufacturing Technology Journal, 2013)
Research paper discuss the possibility of vibration detection on production machine and also presents devices and methodology for evaluation of vibration amplitude using non-contact laser interferometer and contact piezoelectric vibration sensors. Experimentally determines the influence of technological conditions on the quality of functional surfaces. Furthermore, paper evaluates the influence of technological conditions during planar grinding on the vibration amplitude of the grinding spindle and presents correlation between grinder vibration amplitude and quality of the product.
Keywords: Vibration; Grinding; Surface quality; Roughness